The use of qualitative approach to detect and assess potential drug-drug interactions which may decrease the effectiveness of oral contraceptives – pilot study and literature review - Kilińska, Karolina; Cerbin-Koczorowska, Magdalena; Matschay, Arleta; Mierzwicki, Michał; Chmaj-Wierzchowska, Karolina (Journal of Medical Science, 2014)
Aim. The aim of the pilot study was to assess the effectiveness of the tool designed for detecting potential drug-drug interactions of combined oral contraceptives (COCs) with particular emphasis on those which can affect their contraceptive action. A proper study protocol design seems to be essential for further analysis of more data and for establishing correlations between observed interactions and demographic variables.Material and methods. The cross-sectional descriptive, retrospective study was carried out on Polish females from March to May 2013. Gathered data, including products used concomitantly with contraceptive drugs, were derived electronically by patients and underwent thematic analysis.Results. Out of 49 respondents who agreed to participate in the study and fit the inclusion criteria only 15 derived qualitative data about other medicinal products they used. However, some of them sent their monthly report more than once, which gave the total of 158 drugs listed in 25 forms gathered during the whole pilot study. Fifty-three potential drug interactions were found, including 13 (24.53%) which could have decreased the effectiveness of contraceptive drugs.Conclusions. Continuation of the study in accordance with the study protocol will result in identification of common potential drug-related problems, which may enable development of an educational solution for gynecologists, pharmacists and patients increasing their awareness of the potential risk of contraceptive failures and unintended pregnancies.